2018
DOI: 10.1177/2325967118805386
|View full text |Cite
|
Sign up to set email alerts
|

Poor Readability of AOSSM Patient Education Resources and Opportunities for Improvement

Abstract: Background:Appropriate education on the disease processes associated with orthopaedic pathology can affect patient expectations and functional outcome.Hypothesis:Patient education resources from the American Orthopaedic Society for Sports Medicine (AOSSM) are too complex for comprehension by the average orthopaedic patient.Study Design:Cross-sectional study.Methods:Patient education resources provided by the AOSSM were analyzed with software that provided 10 readability scores as well as opportunities for impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…These findings are in accordance with other domains of orthopedic surgery, which have also demonstrated poor readability for patient educational materials. 4 , 5 , 11 , 13 , 15 , 16 , 19 , 20 , 24 In the setting of hip preservation–related educational materials, Parsa et al identified a statistically weak negative correlation between orthopedic institutional rank (ρ = −0.21) and readability. 15 Conversely, the current study was not able to confirm these notions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are in accordance with other domains of orthopedic surgery, which have also demonstrated poor readability for patient educational materials. 4 , 5 , 11 , 13 , 15 , 16 , 19 , 20 , 24 In the setting of hip preservation–related educational materials, Parsa et al identified a statistically weak negative correlation between orthopedic institutional rank (ρ = −0.21) and readability. 15 Conversely, the current study was not able to confirm these notions.…”
Section: Discussionmentioning
confidence: 99%
“…Specific equations for these readability metrics have been detailed in previous studies and are displayed in Table I . 11 , 15 All of these scores, with the exception of the Flesch Reading Ease, provide an output indicating reading difficulty based on grade level (eg, score of 8 equates to 8 th -grade reading level). A linear regression analysis was used to generate variance inflation factors, with values ≥ 10 indicating collinearity between various readability scores.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Patients are sometimes faced with the challenges of understanding and remembering the information in MPIs especially due to the verbosity of the text and usage of technical terms. 33 The average number of words per MPI in this study was 1100. This is comparable with the finding of Joseph et al 6 in Jos Nigeria where the 66 MPIs evaluated had mean word count > 900, but different from the average of 2000 words per MPI reported for German MPIs with a mean of 114.1 difficult words.…”
Section: Discussionmentioning
confidence: 73%
“…This gap continues to grow along with rapid advances in genomic testing technologies that can offer accurate, molecular diagnoses to those previously undiagnosed (Kole & Faurisson 2009; Talwar, Tseng, Foster, Xu, & Chen, 2017). Reliable resources regarding basic genetic concepts, including testing and diagnosis, are available but are generally not targeted to the RD community and are often unreliable or unclear (Aaronson, Joshua, & Boss, 2018; Badiu et al, 2017; Kakazu, Schumaier, Minoughan, & Grawe, 2018; Schoof & Wallace 2014). Healthcare providers may not be equipped to answer genetics‐related questions that arise throughout a patient's RD journey (Litzkendorf et al, 2016).…”
Section: Introductionmentioning
confidence: 99%